Gender Ideology and Women's Labor Market Transitions Within Couples in the Netherlands. Issue 5 (22nd June 2018) - Khoudja, Yassine; Fleischmann, Fenella
Abstract : Objective: This study examines the role of women's and their partners' gender ideology in shaping women's labor market entries, exits, and changes in hours of employment. Background: Recent research argues that women's gender ideology is crucial for understanding women's contemporary labor market participation. However, the role of male partners' gender ideology for partnered women's labor market participation has received less attention. Method: The analysis uses three waves of a large‐scale household panel survey based on a random sample of individuals within Dutch households. Random‐effect models are applied to study whether women's and their partners' gender ideology are associated with women's labor market transitions and whether relevant household characteristics' associations with women's labor market transitions are conditional on both partners' gender ideology. Results: Women's gender ideology is associated with the probability of women's labor market entries and exits, but not with changes in women's hours worked, whereas their male partners' ideology is related only to the probability of women's labor market exits. Furthermore, the negative association of having children with changes in women's hours worked is stronger for traditional compared to egalitarian women. There is no clear evidence that gender ideology moderates the association of the male partner's labor market resources with women's labor market transitions. Conclusion: Women's labor market transitions are not only reactions to economic pressure and institutional constraints but also women's and marginally their partners' gender attitudes.